SUPERVISI KLINIS DALAM UPAYA PENINGKATAN KEMAMPUAN GURU PADA PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 001 LIPAT KAIN KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR TAHUN 2021 - Ridarma (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
The main problem of this thesis is Clinical Supervision in Efforts to Improve Teacher Ability in the Implementation of Islamic Religious Education Learning at SD Negeri 001 Fold Kain, Kampar Kiri District, Kampar Regency. The objectives of this study are, 1) Explaining the process/mechanism of developing Clinical Supervision in an Effort to Improve Teacher Ability in the Implementation of Islamic Religious Education Learning at SD Negeri 001 Fold Kain, Kampar Kiri District, Kampar Regency; 2) Explaining the ability of teachers in the implementation of PAI learning at SD Negeri 001 Fold Kain, Kampar Kiri District, Kampar Regency; 3) to find out the efforts made in improving the ability of teachers in the implementation of PAI learning at SD Negeri 001 Fold Kain, Kampar Kiri District, Kampar Regency.This research is a qualitative research with a phenomenological and scientific approach. The data sources of this research are the Principal, PAI subject teachers,. Data collection techniques were carried out using interview, observation and documentation instruments. The technique of analyzing/processing qualitative data uses three stages, namely 1) data collection; 2) Data reduction; and 3) data presentation; and 4) Drawing conclusions.The results of the research are: 1) Clinical supervision is used to solve problems both in the administration of teaching and learning for PAI teachers to improve PAI teacher performance, through the stages of planning, implementation, monitoring and evaluation; 2) After undergoing clinical supervision, the teacher has insight into learning methods and learning media. Teachers can take advantage of existing media around; and 3) Barriers to the implementation of supervision as an effort to improve the performance of PAI Teachers at State Elementary School 001 Fold Kain, Kampar Kiri District, Kampar Regency, show that several obstacles experienced by school principals in carrying out clinical supervision include: (1) too many teachers who must be supervised clinically, (2 ) lack of clinical supervision time, (3) there are still many weaknesses of teachers in PBM and academic administration, (4) teachers sometimes feel unprepared and disturbed because they are not accustomed to clinical supervision, (5) assessment is only formative, (6) in the learning process some teachers have not used media tools, (7) teachers have limited ability in developing teaching materials and (8) some of the RPP are copy paste. To overcome these obstacles, a planned solution is needed, namely: (1) making a schedule that is in accordance with the conditions of the principal and teacher due to the unbalanced number of teachers and principals who provide clinical supervision (2) solutions provided by the principal adapting to the problems faced by teachers, almost all teachers are weak in the preparation of teaching and learning administration, (3) the solutions provided are classified and prioritized for completion, because not all problems can be solved in the same way and have the same weight, (4) involvement of teachers to help overcome obstacles in the implementation of clinical supervision, (5) solutions are provided by considering psychological, sociological, religious, comfort and other aspects; (6) the need for training/training, short courses, and advanced schools, (7) the role of the principal by providing regular, gradual and continuous coaching, and (8) conducting comparative studies of visitations to more advanced schools.